Retrospective study on prevention of bladder neck contracture by local injection of betamethasone after transurethral resection of the prostate in patients with small-volume prostate - Wang, Qiang; Jiang, Yunlong; Ao, Ping; Huang, Houbao; Zhang, Wenqiang; Yuan, Xiaoxu (Frontiers in Surgery, 2026)
ObjectiveBladder neck contracture (BNC) is a challenging postoperative complication of transurethral resection of the prostate (TURP), especially in patients with small-volume prostates (<40 mL) who are at high risk. This retrospective study aimed to evaluate the efficacy and safety of local betamethasone injection in preventing BNC following TURP in this specific population.MethodsClinical data of 248 patients with small-volume benign prostatic hyperplasia (BPH) who underwent TURP at Zhuhai People's Hospital from January 2017 to December 2023 were retrospectively analyzed. Patients were divided into two groups: the betamethasone injection group (n = 128) receiving 8 mg betamethasone injected into the submucosal layer of the bladder neck (3, 6, 9, and 12 o'clock positions) during surgery, and the control group (n = 120) undergoing TURP without betamethasone injection. All procedures were performed using standardized bipolar plasma TURP without bladder neck incision. Baseline characteristics, intraoperative parameters, and postoperative outcomes were collected. The primary endpoint was the incidence of BNC within 12 months of follow-up, diagnosed based on clinical symptoms, uroflowmetry (maximal urine flow <10 ml/sec), and cystoscopy. Secondary endpoints included the incidence of other postoperative complications.ResultsThe baseline characteristics of the two groups were comparable (all p > 0.05). During the 12-month follow-up, the incidence of BNC in the betamethasone injection group was significantly lower than that in the control group (2.3% vs. 10.8%, p = 0.004). Multivariate logistic regression analysis identified local betamethasone injection as an independent protective factor against BNC (OR = 0.20, 95% CI: 0.06-0.69, p = 0.011), while prostate volume ≤30 mL was an independent risk factor (OR = 3.21, 95% CI: 1.08-9.53, p = 0.036). There were no significant differences in the incidence of other postoperative complications (urinary tract infection, secondary hemorrhage, urethral stricture, urinary incontinence) between the two groups (all p > 0.05).Conclusion: Local injection of betamethasone during TURP significantly reduces the incidence of BNC in patients with small-volume prostates without increasing perioperative complications. This intervention targets the inflammatory and fibrotic mechanisms underlying BNC and serves as a safe and effective adjuvant strategy to optimize surgical outcomes in this high-risk population.